PENGELOLAAN OPINI PUBLIK DALAM MEMBANGUN REPUTASI (Studi kasus pada Humas Pemerintah Kabupaten Bengkalis) - Try Aditia; Hamidi said; Supriati Supriati (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract : The purpose of the research are to know how the public relations officer of Bengkalis regency government managing public opinion, the cons- traints face, and to determine solutions to faced constraints. This type research is descriptive. The results of the research is the public relations officer Bengkalis regency government in managing public opinion that is media monitoring acti- vities, news analysis, discussion results of analysis, and set of information pack- aging strategy. Constraints faced  is society of Bengkalis less familiar media mo- dern, public relations officer does not meet qualifications, and facilities ina- dequate.  The solution is to the public relations activities of conducted intensive- ly, revitalizing public relation officer, and the addition infrastructure required. So that the function and purpose of public relations goes well then the human re- sources that are used by Public Relations of Bengkalis Regency Government fac- tor should prioritize quality over quantity, at least a Public Relations must have the appropriate background to the field. Keywords : Public Relations, Public Opinion